Public administration and public policy: old perspectives, new directions - Reynolds Harry W. Jr.
Public administration has rather studiously avoided serious consideration of its ties to public policy throughout most of this century. The politics/administration dichotomy leaves a lasting legacy. Policy has a central place in the ongoing effort to explain what public administration is and how it functions. Policy defines the purpose of agencies, stipulates much of the detail about their organization, provides authority and legitimacy, and makes them important - probably the most important - instruments of policy effectuation and evaluation. Public administration has traditionally displayed an interest in management; it has been studied, taught, and practiced as method, "how to." This instrumentalist orie
Keywords: Public Policy; Public Administration